From pedestrian area to urban project: assets and challenges for the centre of Brussels - Michel Hubert; Eric Corijn; Julie Neuwels; Margaux Hardy; Sofie Vermeulen; Joost Vaesen (Brussels Studies, 2017)
The new pedestrian area in the centre of Brussels is one of the most important urban projects of the last decades. In 2015, the central traffic artery, Boulevard Anspach, was pedestrianised. The public space and the biggest metro stations must still be renovated. The implementation of this project and the challenges it faces are inherently complex. Experiences in Belgium and abroad show that the impact on the city centre of Brussels will be significant at different levels: the quality of public space; housing and public services; local economy and employment; mobility, logistics and accessibility; and social and cultural activities. However, recent data and analyses are fragmented, non-existent or inaccessible for all stakeholders involved. Nevertheless, an urban project may only succeed when knowledge and expertise are gathered and shared, and used to support decision-making. Therefore, BSI - Brussels Centre Observatory (BSI-BCO) is monitoring this project closely. Previously published research is further developed in this synopsis [Portfolio#1]. Part 1 discusses the context of the project. Part 2 details the four main challenges based on our first observations. The synopsis concludes with concrete scenarios to improve the overall quality and management of the project.